Influence of perhalophenyl groups in the TADF mechanism of diphosphino gold(I) complexes - Soldevilla, Inés; García-Camacho, Aimara; Nasibullin, Rinat T.; Olmos, M. Elena; Monge, Miguel; Sundholm, Dage; Valiev, Rashid R.; López-de-Luzuriaga, José M.; Rodríguez-Castillo, María (Journal of materials chemistry)
New perhalophenyl three-coordinated gold(i) complexes using the chelate ligand 1,2-bis(diphenyl-phosphino)benzene (dppBz) and [AuR(tht)] (R = C6F5 (1), o-C6BrF4 (2), p-C6BrF4 (3), o-C6F4I (4), p-C6F4I (5); tht = tetrahydrothiophene) have been prepared. The crystal structures of compounds 1 and 2 consist of distorted three-coordinated Au(i) complexes displaying different Au-P distances at the same gold atom. The complexes show intense photoluminescent emission in the solid state at room temperature (RT) and at 77 K. The study of the dependence of the emission lifetime with temperature suggests the existence of thermally activated delayed fluorescence (TADF) processes at RT. We have computed the rate constants for intersystem crossing and reverse intersystem crossing of the photophysical processes through first-principle calculations, supporting the experimental observations with very good agreement.